Alternative splicing of the cell fate determinant Numb in hepatocellular carcinoma. Issue 4 (3rd July 2015) - Lu, Yinying; Xu, Wanping; Ji, Junfang; Feng, Dechun; Sourbier, Carole; Yang, Youfeng; Qu, Jianhui; Zeng, Zhen; Wang, Chunping; Chang, Xiujuan; Chen, Yan; Mishra, Alok; et al.
<x xml:space="preserve">Abstract</x> The cell fate determinant Numb is aberrantly expressed in cancer. Numb is alternatively spliced, with one isoform containing a long proline‐rich region (PRRL) compared to the other with a short PRR (PRRS). Recently, PRRL was reported to enhance proliferation of breast and lung cancer cells. However, the importance of Numb alternative splicing in hepatocellular carcinoma (HCC) remains unexplored. We report here that Numb PRRL expression is increased in HCC and associated with early recurrence and reduced overall survival after surgery. In a panel of HCC cell lines, PRRL generally promotes and PRRS suppresses proliferation, migration, invasion, and colony formation. Knockdown of PRRS leads to increased Akt phosphorylation and c‐Myc expression, and Akt inhibition or c‐Myc silencing dampens the proliferative impact of Numb PRRS knockdown. In the cell models explored in this study, alternative splicing of Numb PRR isoforms is coordinately regulated by the splicing factor RNA‐binding Fox domain containing 2 (RbFox2) and the kinase serine/arginine protein–specific kinase 2 (SRPK2). Knockdown of the former causes accumulation of PRRL, while SRPK2 knockdown causes accumulation of PRRS. The subcellular location of SRPK2 is regulated by the molecular chaperone heat shock protein 90, and heat shock protein 90 inhibition or knockdown phenocopies SRPK2 knockdown in promoting accumulation of Numb PRRS. Finally, HCC cell lines that predominantly express PRRL are differentially sensitive to heat shock protein 90 inhibition. Conclusion: Alternative splicing of Numb may provide a useful prognostic biomarker in HCC and is pharmacologically tractable. (Hepatology 2015;62:1122‐1131)